Kemampuan Mahasiswa PGSD dalam Menulis Surat - Linda Puspita (Universitas Negeri Malang, 2016)
The problem raised in this research was the capability of PGSD students in writing formal letter. Data were collected by a test. In this case, the students were asked to write a formal letter in 90 minutes. The lenght of the letter was not limited. The analyses of the data were based on formal letter requirements. Population of this research was students of PGSD of FKIP Universitas Sriwijaya. They were 124 students, and only 30 of them taken were as a sample. The results of this research show thatstudent's capability in writing formal letter falls into four categories: (a) good category 3,33%; (b) fair category 56,66%; (c) bad category 36,66%; and (d) worse category 3,33%. It is suggested that the lecturers give more exercises especially in formal letters, sntence arrangement, using puctuation, and paragraph arrangement